The Solomon four groups plan: A cross-Hispanamerican educational evaluation - Gorenc, Klaus-Dieter (1995)
Two modalities of research design's workshops -long and short- were developed to qualify 658 Hispanamerican research workers, whom were divided into 30 groups, and were applyied along ten years. The terminal efficiency of the workshops was measured with a pre-post-test design and the differences were assessed with a t-test -for dependent samples-. The results showed that the values of the post-test were higher -p ≤ 0.001- than the pretest averages. Contrasting the two workshop versions, the average of the long workshop was significantly higher -p ≤ 0.001- than the short one, by means of a multiple pre-post-test design and the t-test for independent samples. Using Solomon four-group design it was feasible to establish that the significant increase of knowledge about research designs was not influenced by the interaction of the pretest and treatment factors and there was not observed any significant difference between both versions.